Implementasi Backup Koneksi Jaringan Menggunakan Metode Failover MikroTik pada PT Tiga Kawan Sertifikasi - Raharjo, Pratama Putra; Setiawan, Kiki; Kastum (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The internet plays a vital role in supporting business operations in companies or organizations by accelerating the flow of information and enabling real-time connections. According to a report by We Are Social, the number of internet users in Indonesia reached 213 million in January 2023, accounting for about 77% of the total population. However, despite the numerous ISPs in Indonesia, not all internet services are affordable or of high quality, and some areas remain inaccessible to providers using fiber optic connections. PT. Tiga Kawan Sertifikasi, a company engaged in legal services in Tangerang, faces challenges with its internet connection as it relies solely on a single provider, Orbit from Telkomsel. Issues arise when the modem signal frequently drops due to the use of SIM card media instead of fiber optic cables. The proposed solution is to add another provider as an alternative and implement a failover method on a Mikrotik router to ensure a stable connection.